Kompetensi Pejabat Pengelola Keuangan dan Peran Audit Internal Terhadap Kualitas Laporan Keuangan SKPD dengan Komitmen Organisasional Sebagai Variabel Pemoderasi - Hafizhoh, Putri; Misra, Fauzan (E-Jurnal Akuntansi; Vol 33 No 7 (2023), 2023)
The quality of the financial reports of the Regional Work Unit (SKPD) is an instrument that can be used as a guide in making decisions for interested parties. The purpose of this research was conducted to prove empirically the influence of the competence of financial management officials, the role of internal audit, and organizational commitment on the quality of SKPD financial reports in the Municipal Government of Padang Panjang. The sampling procedure used in this research is the saturated sample method with a sample of 72 people. This research utilizes primary data, namely the method of collecting data through questionnaires. The data analysis method utilizes SEM-PLS with the SmartPLS 3.0 application. The results of the study show that the competence of financial management officials and organizational commitment do not affect the quality of financial reports in the Padang Panjang City Government SKPD. Conversely, the role of internal audit has a positive effect on the quality of financial reports in the Padang Panjang City Government SKPD. Keywords: Competence of financial management officials; the role of internal audit; organizational commitment; quality of the financial statements.